Physicochemical properties of seven outstanding strawberry (Fragaria x ananassa Duch.) varieties cultivated in Cundinamarca (Colombia) during maturation - Gerhard Fischer; David López-Valencia; Manuel Sánchez-Gómez; John Fabio Acuña-Caita (Ciencia y Tecnología Agropecuaria, 2018)
The strawberry market in Cundinamarca (Colombia) is mainly size driven with no consideration for its maturation state and nutritional quality, wasting therefore, its organoleptic and nutritional potential. For that reason, the physicochemical differences among seven strawberry varieties (Albión, Dulce Ana, Lucía, Monterrey, Ruby June, Sabrina and Ventana) cultivated in the municipality of Sibaté (Cundinamarca) were established. Fruits collected from a productive plot with homogeneous cultivation management conditions were analyzed in six maturity states, establishing the degree of red pigmentation according to the Colombian Standard ntc 4103. Fresh weight, size, color, firmness, total soluble solids (tss), total titratable acidity (tta), maturity and respiration indices were evaluated. Fruits in stages 4, 2 and 3 developed their largest size and weight, where the variety Dulce Ana stands out. The highest color index values were found in the maturity stage 5 in the variety Ventana. Moreover, the highest firmness values were recorded in stages 4 and 5 in the varieties Monterrey and Ventana. The varieties Sabrina, Dulce Ana and Monterrey accumulated the highest tss concentration and the last two showed the best maturity relations. Respiration rates increased with maturation, especially from stage 3. The results suggest that the optimum commercialization and consumption points are stages 3 and 4, namely because these stages exhibit the highest maturity index and fruit weight. Among the varieties studied, Monterrey stands out due to its firmness and maturity index.